Invited Commentary—“How Support for Black Lives Matter Impacts Consumer Responses on Social Media” - Thomas, Jacquelyn S.; Chintagunta, Pradeep K. (Marketing Science, 2022)
In this commentary of “How Support for Black Lives Matter Impacts Consumer Responses on Social Media,” we discuss issues related to the research approach, findings, and offer suggestions for future research.